2015
DOI: 10.1136/oemed-2014-102726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occupational farming on lung function development in young adults: a 15-year follow-up study

Abstract: We conclude that being a current farmer is associated with a negative effect on lung function, when compared to ex-farmers, with females being more susceptible. Being raised on a farm protects against the adverse effect of BHR on change in lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…Moreover, decreased FVC was measured in compost workers in the cross-sectional study and the first follow-up after 5 years 9 14. However, the longitudinal change of lung function in 1964 bioaerosol-exposed farming students did not differ significantly from that of 407 controls over 15 years 26. This result is also observed in the present work.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, decreased FVC was measured in compost workers in the cross-sectional study and the first follow-up after 5 years 9 14. However, the longitudinal change of lung function in 1964 bioaerosol-exposed farming students did not differ significantly from that of 407 controls over 15 years 26. This result is also observed in the present work.…”
Section: Discussionsupporting
confidence: 78%
“…Information on the participants’ working history, including the number of years of employment and the working hours spent on each type of work for every job held since the beginning of his farming career, was available from the follow-up questionnaire. The cumulative exposure during each employment was calculated as the product of the time-weighted average (TWA) concentration and corresponding work duration in hours per week for stable and fieldwork separately 18. Assuming a 40 hours workweek, the number of work years multiplied by the relevant TWAs was calculated and summed up for each employment period.…”
Section: Methodsmentioning
confidence: 99%
“…FVC change was significantly associated with a factor 2 increase in both endotoxin (−40.7 mL/year) and inhalable dust exposure (−41.2 mL/year). One study from our own group by Bolund et al 36 found no relation between either dust or endotoxin exposure and change in lung function among young farmers.…”
Section: Resultsmentioning
confidence: 87%
“…Two studies34 42 found evidence of effect modification by sex; one study on farmers36 found that the negative effect on lung function from being a current farmer compared with an ex-farmer was larger for females than for males; the other study on wood workers42 showed that female wood workers with the highest exposure had a significant excess decline in FEV 1 (25 mL) compared with the lowest exposure, which was not seen for males. Of those studies that explored effect modification by smoking,36 39 43 no studies found clear indications of significant interaction between smoking and exposure on the decline in lung function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation